The Effect Of Institutional Ownership Profitability and Tax Avoidance On The Cost Of Debt In The Food and Beverage Sub-Sector Listed On The BEI In 2017 - 2022 - Fathurohmah, Nabilah; Valentin, Michel; Gumala Sari, Egi (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2025)
Purpose – This study aims to determine the effect of Institutional Ownership, Managerial Ownership, Profitability and Tax Avoidance on Debt Costs. Design/methodology/approach – This study uses quantitative data, the sample in this study is a food and beverage sub-sector company listed on the Indonesia Stock Exchange in the period 2017 - 2022 as many as 12 companies. The analysis technique used to test the hypothesis is multiple regression analysis using Eviews 9 software. Findings – The results of this study indicate that the Institutional Ownership variable has a negative and statistically insignificant effect on debt costs, the Managerial Ownership variable has a positive and statistically insignificant effect on debt costs, the Profitability variable has a positive and statistically insignificant effect on debt costs, and the Tax Avoidance variable has a negative and statistically insignificant effect on Debt Costs Research limitations/implications – This study discusses Debt Costs and other factors such as Institutional Ownership, Managerial Ownership, Profitability and Tax Avoidance which focus on food and beverage sub-sector companies.